68Ga-DOTATOC PET/CT-Based Radiomic Analysis and PRRT Outcome: A Preliminary Evaluation Based on an Exploratory Radiomic Analysis on Two Patients - Liberini, Virginia; Rampado, Osvaldo; Gallio, Elena; De Santi, Bruno; Ceci, Francesco; Dionisi, Beatrice; Thuillier, Philippe; Ciuffreda, Libero; Piovesan, Alessandro; Fioroni, Federica; Versari, Annibale; Molinari, Filippo; et al. (Frontiers in Medicine, 2021)
Aim: To evaluate whether radiomic features extracted by 68Ga-DOTATOC-PET/CT of two patients are associated with the response to peptide receptor radionuclide therapy (PRRT) in patients affected by neuroendocrine tumor (NET). Methods: This is a pilot report in two NET patients who experienced discordant response to PRRT (responder vs. non-responder), according to RECIST1.1. Patients presented with liver metastasis from rectum and pancreas G3-NET, respectively. Whole-body total-lesion somatostatin receptor-expression (TLSREwb-50) and somatostatin receptor-expressing tumor volume (SRETV wb-50) were obtained in pre- and post-PRRT PET/CT. Radiomic analysis was performed extracting 38 radiomic features (RFs) from the patients’ lesions. The Mann-Whitney test was used to compare RFs in the responder patient vs. non-responder patient. Pearson correlation and Principal Component Analysis (PCA) were used to evaluate the correlation and independence of the different RFs. Results: TLSREwb-50 and SRETVwb-50 modifications correlate with RECIST1.1 response. 28 RFs extracted on the pre-therapy PET/CT showed significant differences among the two patients in the Mann Whitney test (p < 0.05). A total of seven second-order features, with poor correlation with SUVmax and PET volume, were identified by the Pearson correlation matrix. Finally, the first two PCA principal components (PCs) explain 83.8% of total variance. Conclusion: TLSREwb-50 and SRETVwb-50 are parameters that might be used to predict and to assess the PET-response to PRRT. RFs might have a role in defining inter-patient heterogeneity and in the prediction of therapy response. It is important to implement future studies with larger and more homogeneous patient populations to confirm the efficacy of these biomarkers.